Tourism and resource development: a case study of Madhya Pradesh - Pandey, Devendra; Mishra, Satyendra; Shukla, Sandeep (International Journal of Biological Research, 2014)
At present tourism is considered as one of the important economic sector, which impels the growth & development of many of the states of India. Tourism provides a marketable product, which does not depend on raw materials from outside. This paper analyses the problems & strategies for tourism and resource development, which bears great prospects in future development of Tourism. Hospitality, the foundation on which the edifice of Madhya Pradesh tourism built, is indigenous to Madhya Pradesh. Madhya Pradesh sends largest number of travellers to almost every corner of the world, but its strengths to be host is not yet been fully utilized due to the lack of information highway. Madhya Pradesh is also known, as the “Heart of India”. It offers colourful experience to its travellers packed with pleasant surprises, endowed with forest & deserts, hills & plains, & lakes, tribal hinterlands & special interest destination with a strong rail, road, & air network. The Poor infrastructure, ineffectual marketing & inefficient management of resource ensures that tourist steer clear, little wonder then, Madhya Pradesh contribute little over 2% to the total tourist traffic of the country, while neighbouring Rajasthan share is over 4%. The Government policies has been introduced to eradicate the problems associated, but still it is on the paper & will have to travel far long way to reach their destinations. Most of tourism planning in the region appears to be adhoc. Therefore, it is essential to move away from such an ad hoc approach to draw up definite plans of action, charting out the future directions clearly. Keywords: Tourism, Resource Development, Eradication, Hospitality and Infrastructure.